2007
DOI: 10.1002/cvde.200706631
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Gadolinium Oxide Films

Abstract: Thin cubic Gd 2 O 3 films are grown by atomic layer deposition (ALD), in the temperature range 300-400°C, using a novel tris(2,3-dimethyl-2-butoxy)gadolinium(III) precursor, Gd[OC(CH 3 ) 2 CH(CH 3 ) 2 ] 3 , and water. The films are crystalline in their as-deposited state. The films contain some residual hydrogen and carbon, and are probably oxygen-deficient in the as-deposited state, causing flat-band shifts in Gd 2 O 3 -based metal-oxide-semiconductor (MOS) capacitor structures. On the other hand, the permitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…Capacitance/voltage (C-V) data of metal-insulator-semiconductor (MIS) capacitors with 12.5 AE 0.5 nm thick Gd x Al 2- The permittivity was found to increase with Gd content, in keeping with the permittivity values reported for Al 2 O 3 (k $ 8) [42] and Gd 2 O 3 (typically 14-16, [18,19,25,43,44] although higher values up to 24 have also been reported for epitaxial layers [45] [12,13,46] where no large decrease of Full Paper the permittivity with respect to La 2 O 3 was also observed, neither due to Al 2 O 3 incorporation [47] nor due to amorphization. [48] 3.…”
Section: à3supporting
confidence: 80%
See 1 more Smart Citation
“…Capacitance/voltage (C-V) data of metal-insulator-semiconductor (MIS) capacitors with 12.5 AE 0.5 nm thick Gd x Al 2- The permittivity was found to increase with Gd content, in keeping with the permittivity values reported for Al 2 O 3 (k $ 8) [42] and Gd 2 O 3 (typically 14-16, [18,19,25,43,44] although higher values up to 24 have also been reported for epitaxial layers [45] [12,13,46] where no large decrease of Full Paper the permittivity with respect to La 2 O 3 was also observed, neither due to Al 2 O 3 incorporation [47] nor due to amorphization. [48] 3.…”
Section: à3supporting
confidence: 80%
“…Several papers have been published on the deposition and characterization of Gd 2 O 3 using, e.g., e-beam evaporation [18][19][20][21] or radio frequency (RF) sputtering. [22] In addition, ALD was reported using Gd(thd) 3 (thd ¼ 2,2,6,6-tetramethyl-3,5-heptanedionato) in combination with O 3 , [23] or, alternatively, using Gd(CpCH 3 ) 3 (Cp ¼ cyclopentadieentadienyl), [23] Gd(mmp) 3 (mmp ¼ 1-methoxy-2-methyl-2-propoxide), [24] or tris(2,3-dimethyl-2-butoxy)Gd [25,26] in combination with H 2 O. On the other hand, a very limited number of papers report on the deposition of Gd x Al 2-x O 3 thin films, and then only by non-standard techniques, for example, sol-gel deposition.…”
Section: Introductionmentioning
confidence: 97%
“…It is performed by the crystal growth at the nucleation site after RTA, where the crystallization temperature is about 250°C. 20 From Figure 1a and b we can observe that the Gd 2 O 3 -NC dot size is increased with temperature. To find the NC density, top-view transmission electron microscopy ͑TEM͒ images of Gd 2 O 3 -NC memories were analyzed.…”
Section: Methodsmentioning
confidence: 86%
“…Gadolinium orthoaluminate (GdAlO 3 ) mixed oxide possesses excellent magnetic and antiferromagnetic properties [20][21][22]. The pure oxide Gd 2 O 3 is a wide bandgap material (5.37-6.37 eV) [23] and meets the low leakage current requirement in CMOS applications [24]. The superior optical properties of Gd 2 O 3 thin films make them efficient for use in optical applications [23,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The pure oxide Gd 2 O 3 is a wide bandgap material (5.37-6.37 eV) [23] and meets the low leakage current requirement in CMOS applications [24]. The superior optical properties of Gd 2 O 3 thin films make them efficient for use in optical applications [23,25,26]. Hong et al reported that Gd 2 O 3 is an excellent dielectric material to passivate GaAs surface, with a dielectric constant of 10 for epitaxial cubic phase and a low leakage current density of 10 −9 -10 −10 A cm −2 at zero bias [27], while Zhou et al have found out a value of 20 for Gd 2 O 3 thin-film [28].…”
Section: Introductionmentioning
confidence: 99%